2016
DOI: 10.5851/kosfa.2016.36.6.709
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Health Benefit of Highly Marbled Wagyu and Hanwoo Beef

Abstract: This review addresses the characteristics and health benefit of highly marbled Wagyu and Hanwoo beef. Marbling of Wagyu and Hanwoo beef has been increased in Japan and Korea to meet domestic consumer preferences. Wagyu and Hanwoo cattle have high potential of accumulating intramuscular fat (IMF) and producing highly marbled beef. The IMF content varies depending on the feeding of time, finishing diet, and breed type. IMF increases when feeding time is increased. The rate of IMF increase in grain-fed cattle is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…Castration also increased MS in Canadian beef carcasses [ 60 ]. Japanese Black cattle bulls are normally castrated to get highly marbled beef in Japan [ 61 ]. Castration is also known to increase tenderness in several cattle breeds, including Korean cattle [ 62 ], Angus and Angus–Hereford cross breeds [ 63 ], and Brahman and Charolais cross breeds [ 64 ].…”
Section: Management Factorsmentioning
confidence: 99%
“…Castration also increased MS in Canadian beef carcasses [ 60 ]. Japanese Black cattle bulls are normally castrated to get highly marbled beef in Japan [ 61 ]. Castration is also known to increase tenderness in several cattle breeds, including Korean cattle [ 62 ], Angus and Angus–Hereford cross breeds [ 63 ], and Brahman and Charolais cross breeds [ 64 ].…”
Section: Management Factorsmentioning
confidence: 99%
“…While identification of this GO term most likely can be attributed to the aforementioned relationship between steroid hormones and muscle development, as a result of the breed-specific unique high-fat muscle development, it may also be due to the practices under which Hanwoo are reared in order to enhance the natural fat marbling in their meat, such as feeding time and diet. For example, cattle are fed a high-concentration grain diet as opposed to grass-feeding [ 55 ]. Diet has been shown to have an effect on steroid hormones [ 56 ], which may also in part explain the identification of this GO term here.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the higher oleic acid concentration, the proportion of monounsaturated fatty acids (MUFA) in marbled Wagyu and Hanwoo beef was higher. They can lower LDL-C while increasing HDL-C, and may reduce risk for cardiovascular diseases (44). Clinical studies have shown that, low concentrations of SFA C12: 0, C14: 0 are benefit and important for longissimus lumborum muscle of Boer crossbreed goats compared with Santa Inês breed sheep.…”
Section: Discussionmentioning
confidence: 99%